Prognostic significance of ligands belonging to tumour necrosis factor superfamily in acute lymphoblastic leukaemia. Issue 3 (March 2015) - Bolkun, L.; Lemancewicz, D.; Jablonska, E.; Szumowska, A.; Bolkun-Skornicka, U.; Moniuszko, M.; Dzieciol, J.; Kloczko, J.
Highlights Post-induction levels of APRIL but not BAFF or TRAIL are decreased in ALL patients with complete remission (CR). APRIL levels significantly differ between CR MRD-negative and CR MRD-positive ALL patients. Enhanced APRIL levels are associated with shorter leukaemia-free survival and overall survival. Measurements of APRIL levels can improve prognostication in ALL patients.